Physicochemical Characterization and Adsorption Behaviour of Siliceous Soil Towards Aqueous Phosphate - Behera, R.K.; Das, P.S.; Das, R. (Asian Journal of Chemistry, 2013)
The present study was an attempt to use silica rich soil as an adsorbent for removal of aqueous phosphate. Chemical analyses along with powder XRD, TG-DTA and FT-IR spectra showed silica as the major along with Ca/Mg carbonate, iron hydroxide as the minor constituents of the soil. The different of parameters indicated that phosphate adsorption was decreased with increase of pH and initial phosphate concentrations while increased with increase of adsorbent dose. The maximum monolayer adsorption capacity, derived from fitting of adsorption data to Langmuir isotherm, was found to be 17.95 mg P/L.